Debt, Neoliberalism and Crisis: Interview with Maurizio Lazzarato on the Indebted Condition. (October 2014) - Charbonneau, Mathieu; Hansen, Magnus Paulsen
The following presents parts of an interview conducted with Maurizio Lazzarato discussing his 2012 book, The Making of the Indebted Man . In this interview, Lazzarato first elaborates on his theoretical inspirations. Drawing on the work of Deleuze and Guattari in order to connect Nietzsche and Marx, he develops a theory of debt suggesting that the power of credit, central to neoliberalism, requires the construction of an indebted subjectivity. Producing a responsible, guilty and thus hindered subject, this condition involves individuals and societies facing an infinite social debt. According to Lazzarato, post-Fordism should be understood through the ascending influence of neoliberalism, as the state has retroceded its power of money creation to private creditors. Through this process, the relation between capital and labour has been transcended by the creditor–debtor relationship. In the economy of indebtedness, the welfare state is transformed into an inverted Keynesian redistribution system that allows for wealth transfers from non-owners towards owners.